(untitled) (Palíndromo, 2023)
This research investigates the teaching practices for the teaching of color interaction developed by the research project entitled The Painting Studio as a Teaching Laboratory at the State University of Santa Catarina – UDESC. To carry out this research, the general objective was to investigate how proposals for a workshop class on the interaction of colors based on Kandinsky can contribute to the development of pictorial thinking in painting, divided into three specific objectives: (1) analyze the theory of colors in Kandinsky, (2) Present the approach used in conducting taught in the Introduction to Pictorial Language course (3) analysis of data collected from conducting. As a methodology, the qualitative research approach was used, involving the analysis of primary documentary sources of a regency taught to undergraduate students in visual arts and a bibliographic review on the investigated topic. 3 different types of results were obtained considering the pictorial process of the students considering the execution of the exercise that occurred in the following ways: first painting the filter and then the shapes; or the shapes and then a layer of paint to represent the filter; or the interaction of colors in shapes without representing the filter, with this we identified how from the same challenge the students found different ways to solve it, some highlighting the shape, others the interaction of color.